O black metal nos documentários musicais : notas sobre estética e distopia (1994-2017) - Costa, Christiane Santos Alves (2021)
This dissertation aims to understand the dystopian discourse of Black Metal through musical documentaries. It is observed that the speech given in front of the cameras maintains relations with artistic and natural horror, being widely accepted in the social environment as a representation of the musical subgenre. This aesthetic-discursive basis assists in the construction of the cinematographic narrative, guided mainly by those due to the bands, being responsible for the reconstruction of a memory through the image. In this context, the speeches are relevant for the construction and demonstration of attitudes that exceed (or not) a model of common behavior accepted in society, denominated in the research as ―Excess-Artistic‖ (within the standard), and ―Excess of the Extreme‖ (nonstandard). These categories reveal the imaginary contained in the structure of this culture. For the understanding of dystopian aesthetics, the motivation for the adoption of this discourse associated with horror was exposed through the concepts of artistic horror and natural horror (CARROLL, 1999); of aesthetics of evil in Black Metal (CAMPOY, 2008); dystopia (PODOSHEN; VENKATESH; JIN, 2014) and aesthetics of excess (HILDENBRAND, 2015), and how it influences all layers of the subgenre up to the production and dissemination of films, provided here. The methodology used is based on a bibliographic survey, mainly on Black Metal aesthetics; on mapping on cinematography on the topic on Youtube; and in the multi-case study of documentaries. Among the 38 musical documentaries involving Black Metal from 1994 to 2017, the following ones were chosen for this investigation: Det Svarte Alvor (1994), Satan Rides the Media (1998), Once Upon a Time in Norway (2007), Until the Light Takes Us (2008), Black Metal Satanica (2008), One Man Metal (2012), Black Metal Siberia (2015) and Bleu Blanc Satan (2017). The interest was to reflect the importance of these speeches, from their origin in the 90s, until today, in search for a unity, an identity that, possibly, takes on meaning only in the context in which it is inserted: the underground scene. A priori, the conclusion obtained demonstrates the role of musical documentaries as an extension of practices with the underground and the propagation of the common discourse in its midst.